2014
DOI: 10.1186/1472-6920-14-s1-s11
|View full text |Cite
|
Sign up to set email alerts
|

Finding the elusive balance between reducing fatigue and enhancing education: perspectives from American residents

Abstract: Duty hour restrictions for residency training were implemented in the United States to improve residents’ educational experience and quality of life, as well as to improve patient care and safety; however, these restrictions are by no means problem-free. In this paper, we discuss the positive and negative aspects of duty hour restrictions, briefly highlighting research on the impact of reduced duty hours and the experiences of American residents. We also consider whether certain specialties (e.g., Emergency Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Despite acknowledging that fatigue may impair functionality similar to a blood alcohol level >0.05%, RANZCOG does not endorse any limit on the volume of procedures or length of time at work, citing ‘training issues’ as a significant factor in the working hour debate . Internationally, there are legitimate concerns that the compressed workload arising from restricted work hours impacts on specialty training with junior doctors struggling to view the same number of cases in a shorter period of time . A previous Australian study reported that many RANZCOG trainees lacked confidence in performing surgical procedures at the completion of training, but there was no measurement of working hours in this study …”
Section: Introductionmentioning
confidence: 82%
“…Despite acknowledging that fatigue may impair functionality similar to a blood alcohol level >0.05%, RANZCOG does not endorse any limit on the volume of procedures or length of time at work, citing ‘training issues’ as a significant factor in the working hour debate . Internationally, there are legitimate concerns that the compressed workload arising from restricted work hours impacts on specialty training with junior doctors struggling to view the same number of cases in a shorter period of time . A previous Australian study reported that many RANZCOG trainees lacked confidence in performing surgical procedures at the completion of training, but there was no measurement of working hours in this study …”
Section: Introductionmentioning
confidence: 82%
“…By the end of training, resident physicians should be able to practice independently [ 25 ]. There has been much concern that reduced working hours will reduce the clinical exposure of residents, provide less continuity of care, interfere with daytime teaching programs, and reduce exposure to night-time emergency situations [ 26 ]. The reduced patient experience is especially of concern in the procedural specialties where residents are expected to assist or perform a prescribed number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The first set of papers in this issue address the intersection of duty hours with patient safety [ 9 ], resident well-being [ 10 ], the health system [ 11 ], and teaching faculty [ 12 ]. In the next eight papers, we present perspectives from different jurisdictions around the globe, including a detailed exploration of the challenges and current conditions in Sweden [ 13 ], the United States [ 14 , 15 ], Canada [ 16 , 17 ], the United Kingdom [ 18 ], and Australia [ 19 ], with articles written from the perspectives of both residents and faculty. In this section, we also include papers that address the unique considerations for procedural disciplines [ 20 ], as well as the impact of duty hour changes on professionalism [ 21 ].…”
Section: In This Issuementioning
confidence: 99%